2015
DOI: 10.1073/pnas.1424987112
|View full text |Cite
|
Sign up to set email alerts
|

How many proteins does it take to gate hair cell mechanotransduction?

Abstract: Components of the Mechanotransducer ComplexMechanosensory hair cells of the inner ear transduce sound or head motion into electrical signals through the gating of mechanically coupled ion channels. Although many cell types can respond to mechanical force (1), the disposition of mechanotransduction (MT) channels to the very tips of stereocilia (2, 3) confers onto hair cells of the inner ear their specialized sensitivity (4, 5). Differential deflection of the stereociliary tips is transmitted to the MT channels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Association of TMC1 and TMC2 with other MET proteins to form a stable complex may explain TMC1 enrichment at stereocilia tips even after tip link disruption by BAPTA. Other proteins, such as PCDH15 and TMIE, which were recently shown to interact with TMC proteins (Beurg et al, 2015; Fuchs, 2015; Maeda et al, 2014) and TMHS/LHFPL5 identified as an MET channel accessory component (Xiong et al, 2012) may contribute to the spatiotemporal distribution of TMC1 and TMC2 in stereocilia. Similar to TMC, PCDH15 remains at stereocilia tips following BAPTA treat ment (Indzhykulian et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Association of TMC1 and TMC2 with other MET proteins to form a stable complex may explain TMC1 enrichment at stereocilia tips even after tip link disruption by BAPTA. Other proteins, such as PCDH15 and TMIE, which were recently shown to interact with TMC proteins (Beurg et al, 2015; Fuchs, 2015; Maeda et al, 2014) and TMHS/LHFPL5 identified as an MET channel accessory component (Xiong et al, 2012) may contribute to the spatiotemporal distribution of TMC1 and TMC2 in stereocilia. Similar to TMC, PCDH15 remains at stereocilia tips following BAPTA treat ment (Indzhykulian et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the tip link proteins, the molecular composition of the MET apparatus remains elusive (Fuchs, 2015; Gillespie et al, 2005). The tetraspanin TMHS/LHFPL5 (Beurg et al, 2015; Xiong et al, 2012) and a protein with two transmembrane domains, TMIE (Zhao et al, 2014), have recently been identified as MET channel accessory components.…”
Section: Introductionmentioning
confidence: 99%